“They are humans and humanity comes first”: The function of attitudes towards people seeking asylum in Australia - Hartley, Lisa; Pedersen, Anne (2020)
Previous research has found that while many Australians are hostile to people seeking asylum in Australia who arrive by boat (hereafter called asylum seekers), others feel that Australia’s treatment of asylum seekers is inhumane. Two bodies of research that can help us understand why people think the way that they do are the function of attitudes research and the values framework as per Schwartz (1992). In the present study, we use these frameworks to explore what underpins attitudes (both positive and negative) towards asylum seekers. A total of 164 Australian community members completed a mixed-methods questionnaire in 2017 investigating why they felt the way that they did about asylum seekers. Quantitative analyses indicated that the most frequently reported function of attitudes was value-expressive, followed by experiential-schematic, and then indirect experiential-schematic. Qualitative analyses (N = 132) indicated that while both accepting and rejecting participants reported similar values, the most important value reported by accepting participants was Universalism and the most important value reported by rejecting participants was (Un)fairness. Two other values were less reported by both groups: Security and Conformity. Our results take previous findings about attitude function and values further by combining quantitative and qualitative analyses to get a richer picture of Australian attitudes towards people seeking asylum.